BREWSTER'S TRADE MARK APPLICATION. Issue 9 (5th February 2019) - ,
Abstract: H1 Trade marks – Application for registration – BREXIT – Well-known terms – Assessing distinctiveness – State of the register evidence – Parallel Board of Appeal decision – Origin distinctiveness – Appeal to Appointed Person